Effectiveness Of Village Fund Management In Improving Community Welfare In Mangalle Village - Sofyan, Sofyan .S; Anwar, Suhardi M.; Wahida, Altri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to describe the effectiveness of village fund management in improving community welfare in Mangalle Village, Mappedeceng District, North Luwu Regency. Methodology:This study used a qualitative method with a descriptive approach and data collection techniques through observation, interviews, and documentation. The research was conducted over a two-month period. The research informants consisted of village officials and the Mangalle Village community. Results: The results showed that the management of village funds has been running effectively, with implementation in accordance with the stages of planning, implementation, and supervision. This effectiveness is reflected in the achievement of community welfare indicators including social justice, economic justice, and democratic justice. Social justice can be seen from increased access to education, health, and fulfillment of basic needs. Economic justice is achieved through increased income and home ownership, as well as support for agricultural infrastructure. Meanwhile, democratic justice is reflected in a sense of security and openness of public information. The active participation of the community in village meetings also strengthens the accountability of fund management. Findings: Although the management of village funds has fulfilled the welfare of the community, there are still obstacles such as delays in reporting and the existence of websites in the reporting system, as well as budget transfers in the management of village funds and the lack of security programs for the village community. The village government has shown its commitment to continue improving the existing system in order to achieve the overall welfare of the community. Novelty: This study provides insight into the effectiveness of village fund management based on indicators of social justice, economic justice, and democratic justice for the welfare of the community. Conclusion: ultimately, this study is expected to help Mangalle village and become a model for other villages in managing their finances wisely. Paper type: descriptive qualitative research